Bitcoin – Analysis and Application - Vavrovič, Maroš (2014)
In the bachelors thesis I analyze number one virtual currency -- Bitcoin. The main objectives are to answer fundamental questions of Bitcoin users, determine its potential, benefits and threats along with possible application for individuals and businesses. The thesis is divided into three sections that introduce virtual currencies, analyze Bitcoin and point out application opportunities. Analysis of Bitcoin determines its value and monetary background together with main threats threatening numerous users. I analyzed several datasets, resolved potential outcomes and compared them to standard currencies and popular payment channels. Furthermore, the thesis covers popular ways of spending and using Bitcoin for individual users as well as opportunities for businesses.